Petrophysical Investigation of the Khurmala Formation in Taq Taq Oil Field, Zagros Folded Belt - Rashid, Fraidoon; Hussein, Devan O.; Zangana, Hawar A. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2020)
The Tertiary rocks of Khurmala Formation in the Taq Taq oil field have been studied using wireline log analysis, drilling cutting descriptions with integration of mud logging report, and test results for understanding reservoir potentiality and fluid distribution. The formation comprised dolostone and dolomitic limestone with an intercalation of clay layers between the recognized beds. The formation has variable thickness throughout the field, 99.8 m from the northeastern limb and 109 m in the southeastern plunge. The calculated shale volume in the studied interval shows a high rate of the clay contents which in some points the gamma ray has 100% of shale. The corrected log-derived bulk porosity subdivided the Khurmala Formation into 5 porosity units from the top to the bottom including (Kh-1, Kh-2, Kh-3, Kh-4, and Kh-5). The first (Kh-1), third (Kh-3), and fifth (Kh-5) porosity units have the average porosity ≥0.10 (10%) that can be considered as good reservoir unit in terms of porosity, whereas the shale contents reduced the reservoir quality of these units. However, well hydrocarbon entrapment through interconnected fractures and fault in the other Tertiary reservoir was recorded in Taq Taq field , but the weak connectivity of the pores in the Khurmala Formation caused this rock interval remains as water bearing zone.